Analysis of Risk Factors in COVID-19 Adult Mortality in Russia - Youri Kirillov; Sergei Timofeev; Ashot Avdalyan; Vladimir N. Nikolenko; Leonid Gridin; Mikhail Y. Sinelnikov (SAGE Publishing, 2021)
Background and Objective Epidemiological data obtained during the ongoing SARS-CoV-2 pandemic suggests that COVID-19 mortality has specific age and gender associations. However, limited epidemiological studies explored specific populational risk factors, including comorbidities, and patient clinical characteristics. The main aim of our retrospective cohort study was to analyze associations between age, gender, and comorbidities in deceased COVID-19 patients. Materials and Methods A retrospective cohort analysis was performed to assess significant risk factors in adult patients deceased from COVID-19 infection by evaluating Electronic Medical Records and post-mortem analysis in COVID-19 patients deceased between April 2020 to October 2020. All patients underwent post-mortem evaluation along with medical history analysis, including data on disease duration, hospitalization, and clinical peculiarities. Results Medical records of 1487 COVID-19 patients revealed that the prevalence of males was higher (by 23%) than females; the median age for males was 71 years of age whereas for females it was 78. The most prevalent comorbid pathologies were: hypertension, obesity, diabetes, and cancer. Males are at significantly increased risk of lethal outcome, even in younger age groups, with comorbid conditions. Conclusion The study concluded that comorbidities, such as hypertension, obesity, diabetes, cancer are the most important risk factors for comorbid mortality in COVID-19 patients. In addition to lung damage, multiple organ dysfunctions may be a crucial reason for COVID-19 induced death. Special precautions, such as early hospitalization, increased monitoring, and preventative tactics should be taken for at-risk patients.